Architectural and engineering design criteria for earthquake resistant masonry infilled RC frames containing openings - Penava, Davorin (Array, 2020)
In earthquake resistant design of RC frame structures, the definition of masonry infilled frame is often split between reinforced concrete and the masonry structures. However, it is known that the frame elements and the masonry wall work as a coupled system. Additionally, a dedicate chapter for the definitions of openings size, quantity and position is missing. The definition of a full, partial or non-masonry infilled frame with opening is not establish in engineering and architectural codes; rather, recommendations are given. A competent masonry infilled frame with openings would mean to correlate the architectural and engineering concepts as to define an engineered or non-engineered infilled wall. Likewise, certain boundaries should be established using both the architectural and engineering concepts to relate the importance of illumination and air ventilation product of the openings and masonry infilled frame failure patterns.